DIGITALIZATION OF THE ECONOMY AS A BASIS FOR INNOVATIVE DEVELOPMENT OF SOCIETY (American Journal of Interdisciplinary Research and Development, 2025)
The role and features of the digitalization of the economy, which is an objective prerequisite for the innovative development of the state economic system, are revealed, and the results are studied and the prospects for the implementation of the digital economy in the countries of the post-Soviet space are determined. The features of digital representation of information, prerequisites, implementation and consequences of digitalization are considered. An analysis of the relationship between the concepts of "digitization", "digitalization", "digital economy", "digital transformation" is carried out based on the study of the specific features of these categories as a process, application and implementation of its results in building business models. The advanced experience of digitalization development in a number of countries of the post-Soviet space is studied. The forms and methods of assessing the degree of digitalization coverage of Uzbekistan are considered to obtain new opportunities for the use of digital technologies in business, the creation of information technology platforms, new values, benefits, and the provision of virtual services. It is proposed to intensify cooperation between IT companies of the countries in such areas as media content, e-commerce, e-government, digital banking technologies, exchange of experience, the development of innovation centers, the management of technology parks and the development of technological infrastructure. The important role of private business in stimulating the use of the results of the digital economy is noted.